PENGARUH KONDISI PENYIMPANAN OBAT TERHADAP KUALITAS TABLET VITAMIN C DI PUSKESMAS KECAMATAN PONTIANAK KOTA - ., Nova Lestari (Jurnal Mahasiswa Farmasi Fakultas Kedokteran UNTAN, 2013)
Ascorbic acid is a compound that unstable, easily oxidized when exposedto aerial (oxygen) and this process can be accelerated by heat. The purpose of thisresearch is to see the influence of storage conditions on the quality of drugsphysical and chemical tablets of ascorbic acid at the district health centers whichincludes Kampung Bali, Alianyang, Pal tiga and Karya Mulia with differentstorage conditions in each health centers. The method used is non-experimental,and use probability sampling method with simple random sampling. Samplingwas conducted during two months. In this research, do measurement temperature,humidity and evaluation test tablets that include test physical appearance,uniformity of weight, uniformity of size, friability, hardness, disintegration time,dissolution and value, then the results were analyzed statistically using One WayANOVA and Kruskal Wallis. The results showed that ascorbic acid tablets in thefirst and second health center in Kampung Bali, Alianyang, and Pal tigaparameters qualify the uniformity of weight, disintegration time and dissolution,while the Karya Mulia of community health center tablets meets all requirementsof ascorbic acid tablets are good, except the value parameters and uniformity ofsize. Based on the results of this research concluded that the influence of theconditions and duration of storage of drugs affecting the quality of ascorbic acidtablets. Statistical analysis evaluating ascorbic acid tablets between each healthcenters in the first month and the second shows that the health center Karya Muliashowed a significant difference with health center Kampung Bali, Alianyang andPal tiga.Keyword: Ascorbic acid Tablets, Health Centers, Storage Conditions